Fuel cell catalyst layer and proton membrane chemical attenuation accelerated aging test device and test method thereof
By designing a chemical attenuation aging test device for fuel cell catalytic layer and proton membrane chemical decay acceleration aging, using specific solutions and gas to activate samples, simulate the aging process of proton exchange membrane in the operating environment of fuel cell, and solve the problem of difficulty in effectively simulating the aging process in the prior art. , effective evaluation of the durability of proton exchange membrane and catalytic layer is achieved.
Patent Information
- Application Number
- CN202411575270.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively simulate the aging process of the proton exchange membrane in the operating environment of fuel cells, and the durability of the catalytic layer is not fully examined.
Design a fuel cell catalytic layer and proton membrane chemical decay accelerated aging test device, and activate samples of samples with specific concentrations of the solution to be tested and gases are activated, simulate the actual attenuation environment, and evaluate proton exchange by collecting and analyzing F-ion concentrations. Aging of the membrane.
The device can well simulate the actual attenuation situation, provide accurate results of proton exchange membrane aging tests, and provide a new attenuation acceleration method for the durability study of the catalytic layer.
Smart Images

Figure CN119470233A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen fuel cell gas membrane electrode and proton exchange membrane testing, and specifically relates to a fuel cell catalyst layer and proton membrane chemical decay accelerated aging testing device and a testing method thereof. Background Art
[0002] In the process of implementing the present invention, the inventors found that the prior art has at least the following problems:
[0003] The massive consumption of fossil energy has led to increasingly severe energy shortages and environmental problems. In the current global energy transition, it is urgent to develop energy conversion and storage technologies related to clean energy to reduce the proportion of fossil energy in energy consumption and achieve low-carbon development of society. The development of highly promising new energy technologies, such as proton exchange membrane fuel cells and all-vanadium liquid flow batteries (VRFBs), is inseparable from the research on proton exchange membranes (PEMs), the core components directly related to energy conversion efficiency.
[0004] In the preparation of key fuel cell components, fuel cell assembly processes, BOP pipelines and other materials, various impure metal ions are often introduced, which pose a great challenge to the chemical stability of perfluorosulfonic acid. On the other hand, during the operation of the fuel cell, a two-electron reaction often occurs, which produces free radicals. The free radicals are more aggressive to perfluorosulfonic acid under the catalytic action of metal ions. The metal ion impurities introduced by the fuel cell and the free radicals produced by the side reactions will attack the side chains of the perfluorosulfonic acid resin, leading to the decomposition of perfluorosulfonic acid, the loss of the three-phase interface of the catalyst layer, the aging of the proton exchange membrane, and the occurrence of gas permeation, resulting in local hot spots in the fuel cell, performance degradation, and even the risk of burning the stack.
[0005] Existing studies on the chemical durability of proton exchange membranes often use immersion in H2O2 or Fenton's reagent. This chemical accelerated aging experiment can well examine the chemical stability of the proton exchange membrane, but it cannot well simulate the operating environment of the battery and the state of the proton membrane. And it does not propose a new attenuation method for the durability of the catalyst layer. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device and test method thereof, which solves the problem of metal ions, free radicals on proton exchange membranes and resin chemical aging test.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device, comprising:
[0009] Coordinated base and cover plates;
[0010] The workpiece positioning area is arranged on the bottom plate and the cover plate, and the workpiece positioning area can position and encapsulate the sample to be tested.
[0011] A frame is arranged on the outer periphery of the bottom plate, and the frame is sealed and connected to the cover plate.
[0012] The frame is provided with a series of positioning holes, and the frame is connected to the cover plate through the positioning holes and connecting bolts.
[0013] The test method of the above-mentioned fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device is characterized by comprising the following steps:
[0014] 1) Prepare the solution to be tested;
[0015] 2) After packaging the sample to be tested, place it in the fixture of the above-mentioned testing device;
[0016] 3) Prepare KOH solution;
[0017] 4) Connect the entire device and perform leak detection;
[0018] 5) Introduce gas to activate the sample to be tested;
[0019] 6) Add the prepared test solution into the test device, replace the device for collecting the solution with KOH solution, and start the test;
[0020] 7) Weigh the mass of the collected water and calculate F - ion;
[0021] 8) Take out the sample to be tested and conduct further characterization and analysis on the sample.
[0022] In the above step 1), a solution of a specific concentration is prepared, and the solution is H2O2, Fenton solution, Al2(SO4)3, Fe2(SO4)3, CuSO4, Mg2SO4, Cr2(SO4)3 or NiSO4. If the metal element is to be investigated, its anion group is SO4. 2- .
[0023] In the above step 2), the fixture material does not contain metal element impurities, and the samples to be tested include PEM, CCM or GDE.
[0024] In the above step 4), first place pure water in the humidification and condensation devices, connect the entire device, and perform leak detection; set the temperature of the insulation belt to 110°C to ensure that the steam does not condense in the pipeline, and set a specific temperature of the solution to be tested.
[0025] In step 5), the gas was introduced for 16 hours to activate the sample to be tested and to test it. The gas flow rate is related to the area and the gas flow rate is 0.01-0.5 slpm / cm 2 , the gas is an inactive gas.
[0026] In the above step 6), after continuously passing the gas for 16 hours, the prepared solution to be tested is added to the test device, the device for collecting the solution is replaced with KOH solution, and a leak test is performed; the gas is passed for 10 to 500 hours; the gas flow rate is related to the area, and the gas flow rate is 0.01 to 0.5 slpm / cm 2 , the gas is inactive gas; and the test solution and KOH solution are replaced every 24 hours.
[0027] In step 7), the mass of the collected water is weighed, and the concentration of fluoride ions in the retained potassium hydroxide solution is measured by ion chromatography to calculate the released F - ion.
[0028] PEMFCs are mainly composed of a membrane electrode (MEA, including a gas diffusion layer, a catalyst layer, and PEMs) and a bipolar plate as its core. During operation, hydrogen loses electrons at the anode and becomes protons, which pass through the PEM and react with oxygen at the cathode to produce water. As the core material of the membrane electrode, the proton exchange membrane should have the following functions: (1) high proton conductivity, efficient proton transmission, and promotion of anode and cathode reactions; (2) low material permeability to prevent fuel penetration from causing a decrease in energy density and prevent hydrogen and oxygen mixing from causing attenuation; (3) good thermal stability and mechanical strength stability; (4) good chemical stability, and the ability to maintain stability under free radical attacks; (7) low price.
[0029] The mainstream proton exchange membrane is mainly composed of perfluorosulfonic acid resin (PFSA) cast ePTFE. PFSA is copolymerized with tetrafluoroethylene monomer and perfluorosulfonyl fluoride ether monomer. The high bond energy of the CF bond makes the PFSA membrane based on the carbon fluorine skeleton have excellent chemical stability and mechanical properties. The strong electron-withdrawing effect of the fluorinated side chain stabilizes the negative charge, making the sulfonic acid group (-SO3H) connected to the end of the side chain easy to dissociate in water. PFSA has extremely strong acidity (pKa is about -5.5--6), which is conducive to proton conduction. The molecular structure of components with large differences in hydrophilic and hydrophobic polarity connected by covalent bonds allows PFSA to self-assemble to form a microphase separation structure. Thanks to the unique chemical composition and microphase separation structure, PFSA has excellent chemical stability and good proton conductivity. PFSA resin is not only used for the preparation of membranes, but also for the formation of the three-phase interface in the catalytic layer, the bonding of catalysts, and the establishment of water vapor transmission channels.
[0030] One of the above technical solutions has the following advantages or beneficial effects: it solves the problem of metal ions and free radicals on the chemical aging test of proton exchange membranes and resins. It can well simulate the actual attenuation. The test results of the same thickness and air permeability coefficient are similar, which well reflects the actual attenuation. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of a fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device provided in an embodiment of the present invention;
[0032] Figure 2 for Figure 1 Schematic diagram of the fixture of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device;
[0033] Figure 3 for Figure 1 Schematic diagram of the fixture of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device;
[0034] Figure 4 for Figure 1 Schematic diagram of the fixture of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device;
[0035] Figure 5 for Figure 1 The test data diagram of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device;
[0036] Figure 6 for Figure 1 The test data diagram of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device;
[0037] Figure 7 for Figure 1 The test data diagram of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device;
[0038] The markings in the above figures are: 1. bottom plate, 11. frame, 12. positioning hole, 13. workpiece positioning area, 2. cover plate, 3. connecting bolts. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Embodiment 1
[0041] See also Figures 1 to 7 A fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device comprises: a base plate 1 and a cover plate 2 that cooperate with each other; a workpiece positioning area 13, which is arranged on the base plate 1 and the cover plate 2, and the workpiece positioning area 13 can position and encapsulate the sample to be tested.
[0042] A frame 11 is disposed on the outer periphery of the bottom plate 1 , and the frame 11 is sealed to the cover plate 2 to achieve a sealing effect.
[0043] A series of positioning holes 12 are provided on the frame 11 , and the frame 11 is connected to the cover plate 2 via the positioning holes 12 and the connecting bolts 3 .
[0044] The test device is mainly composed of three parts: humidification part, test fixture, and condensation part. These three parts are connected by PTFE tubes, and there is an insulation layer on the outside of the PTFE tube to maintain the temperature at 110°C to ensure that water vapor will not condense in the pipeline. The solution to be tested is a certain concentration of the element or solution to be examined. The test fixture is as shown in the figure above. The material is graphite or PTFE without metal ion impurities to avoid interference with the test results. The flow field on the end plates on both sides is machined according to the actual flow field. The specific flow channel can be determined by the designed flow channel, and this patent takes the multi-snake flow channel as an example.
[0045] First, a solution of specific metal ions and specific concentration is prepared according to the test purpose, and is placed in a first conical flask and heated to a set temperature; the sample to be tested is encapsulated with a frame 11, placed in a specific fixture made of PTFE material, and the fixture temperature is set; nitrogen is introduced for a certain period of time to perform leak detection to ensure sealing; nitrogen is introduced at a certain flow rate, and the gas is passed through the solution to be tested to form a certain humidified gas and bring out a certain amount of solution; the gas is passed into the sample fixture through a PTFE tube with an external insulation layer; the gas after passing through the fixture enters the KOH solution through the PTFE tube with an external insulation layer; the KOH solution absorbs the released F - ions, and passed the test F - The ion concentration can be used to determine the amount of perfluorosulfonic acid released in the sample to be tested. - Ion rate.
[0046] The sample to be tested may be a proton exchange membrane, CCM, or GDE. If the solution to be tested contains metal ions, an ICP test may be performed on the sample to be tested after the test is completed, and the accumulation effect of metal ions in the fuel cell may be obtained.
[0047] Solve the problem of metal ions and free radicals on proton exchange membrane and resin chemical aging test. It can simulate the actual attenuation situation very well. The test results of the same thickness and air permeability coefficient are similar, which well reflects the actual attenuation situation.
[0048] Embodiment 2
[0049] The test method of the above-mentioned fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device comprises the following steps:
[0050] 1) Prepare the solution to be tested;
[0051] 2) After packaging the sample to be tested, place it in the fixture of the above-mentioned testing device;
[0052] 3) Prepare KOH solution;
[0053] 4) Connect the entire device and perform leak detection;
[0054] 5) Introduce gas to activate the sample to be tested;
[0055] 6) Add the prepared test solution into the test device, replace the device for collecting the solution with KOH solution, and start the test;
[0056] 7) Weigh the mass of the collected water and calculate F - ion;
[0057] 8) Take out the sample to be tested and conduct further characterization and analysis on the sample.
[0058] In the above step 1), a solution of a specific concentration is prepared, and the solution is H2O2, Fenton solution, Al2(SO4)3, Fe2(SO4)3, CuSO4, Mg2SO4, Cr2(SO4)3 or NiSO4. If the metal element is to be investigated, its anion group is SO4. 2- .
[0059] In the above step 2), the fixture material does not contain metal element impurities, and the samples to be tested include PEM, CCM or GDE.
[0060] In the above step 4), first place pure water in the humidification and condensation devices, connect the entire device, and perform leak detection; set the temperature of the insulation belt to 110°C to ensure that the steam does not condense in the pipeline, and set a specific temperature of the solution to be tested.
[0061] In step 5), the gas was introduced for 16 hours to activate the sample to be tested and to test it. The gas flow rate is related to the area and the gas flow rate is 0.01-0.5 slpm / cm 2 , the gas is an inactive gas.
[0062] In the above step 6), after continuously passing the gas for 16 hours, the prepared solution to be tested is added to the test device, the device for collecting the solution is replaced with KOH solution, and a leak test is performed; the gas is passed for 10 to 500 hours; the gas flow rate is related to the area, and the gas flow rate is 0.01 to 0.5 slpm / cm2 , the gas is inactive gas; and the test solution and KOH solution are replaced every 24 hours.
[0063] In step 7), the mass of the collected water is weighed, and the concentration of fluoride ions in the retained potassium hydroxide solution is measured by ion chromatography to calculate the released F - ion.
[0064] Solve the problem of metal ions and free radicals on proton exchange membrane and resin chemical aging test. It can simulate the actual attenuation situation very well. The test results of the same thickness and air permeability coefficient are similar, which well reflects the actual attenuation situation.
[0065] Embodiment 3
[0066] The test method of the above-mentioned fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device comprises the following steps:
[0067] S1: Prepare a solution of a specific concentration to be tested. The solution may be H2O2, Fenton solution, Al2(SO4)3, Fe2(SO4)3, CuSO4, Mg2SO4, Cr2(SO4)3, NiSO4, etc. If the metal element is to be tested, the best anion group is SO4. 2- , in order to reduce the impact of anion groups on performance;
[0068] S2: After the sample to be tested is packaged, it is loaded into the above-mentioned fixture. The fixture material should not contain metal element impurities to avoid impurity interference. The sample to be tested can be PEM, CCM, or GDE.
[0069] S3: Prepare a KOH solution of a certain concentration to collect the released F - ions, and then the F in the retained potassium hydroxide solution was measured using ion chromatography. - Ion concentration;
[0070] S4: First, place pure water in the humidification and condensation devices, connect the entire device, and perform leak detection. Set the temperature of the insulation belt to 110°C to ensure that the steam does not condense in the pipeline, and set a specific temperature for the solution to be tested;
[0071] S5: A certain flow of gas is introduced for 16 hours to activate the sample to be tested and to test it. The gas flow rate is related to the area and the gas flow rate is 0.01-0.5slpm / cm 2 , the gas may be an inactive gas such as nitrogen;
[0072] S6: After continuous flow for 16 hours, replace the prepared test solution with the device for the test solution, replace the KOH with the device for collecting the solution, and check for leaks; pass a certain flow of gas, and continue to pass for 10 to 500 hours. The gas flow rate is related to the area, and the gas flow rate is 0.01 to 0.5 slpm / cm 2 The gas can be an inactive gas such as nitrogen; and the test solution and KOH solution are replaced every 24 hours to prevent the solution from evaporating too much and affecting the concentration; to prevent H2O2 or Fenton's reagent from being completely decomposed; to prevent the collection tank from being full;
[0073] S7: Weigh the mass of the collected water and use ion chromatography to measure the fluoride ion concentration in the retained potassium hydroxide solution to calculate the released F - Ion content;
[0074] S8: Take out the sample to be tested, perform further characterization analysis on the sample, and observe the degree of sample attenuation caused by the ion (or solution).
[0075] Solve the problem of metal ions and free radicals on proton exchange membrane and resin chemical aging test. It can simulate the actual attenuation situation very well. The test results of the same thickness and air permeability coefficient are similar, which well reflects the actual attenuation situation.
[0076] Embodiment 4
[0077] The test method of the above-mentioned fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device comprises the following steps:
[0078] S1: After analysis and calculation, a fuel cell engine BOP and stack will produce 0.02ppm Fe 3+ ions, 0.015ppm Al 3+ ions and 0.01ppm Cr 3+ ions, and in addition, the effect of H2O2 produced by the side reaction on the chemical durability of the two membranes was considered.
[0079] S2: In order to accelerate the aging experiment, a solution with a concentration ten times the target concentration was prepared, that is, a solution of 0.075ppm Al2(SO4)3, 0.1ppm Fe2(SO4)3, 0.05ppm Cr2(SO4)3, and 15%wt H2O2 was prepared;
[0080] S3: After the samples to be tested are packaged, they are placed in the above-mentioned fixture. The fixture material should not contain metal impurities to avoid interference from impurities. The samples to be tested are named PEM-1 and PEM-2;
[0081] S4: Prepare 0.1 mol / L KOH solution to collect the released F -ions, the fluoride ion concentration in the retained potassium hydroxide solution was measured using ion chromatography after the durability test;
[0082] S5: Connect the whole device and perform leak detection. Set the temperature of the solution to be tested to 80°C, the temperature of the test fixture to 80°C, and the temperature of the insulation belt to 110°C to ensure that there is no condensation of steam in the pipeline;
[0083] S6: A certain flow of gas is introduced for 16 hours to activate the sample to be tested and to test it. The gas flow rate is related to the area and the gas flow rate is 0.01-0.5slpm / cm 2 , the gas may be an inactive gas such as nitrogen;
[0084] S7: After continuous flow for 16 hours, replace the prepared test solution with the device for the test solution, replace the KOH with the device for collecting the solution, and check for leaks; pass a certain flow of gas, and continue to pass for 100 hours. The gas flow rate is related to the area, and the gas flow rate is 0.01~0.5slpm / cm 2 The gas can be inactive gas such as nitrogen; and the test solution and KOH solution are replaced every 24 hours to prevent excessive evaporation of the solution and affect the concentration; to prevent H2O2 or Fenton's reagent from being completely decomposed; to prevent the collection tank from being full;
[0085] S8: Weigh the mass of the collected water and use ion chromatography to measure the fluoride ion concentration in the retained potassium hydroxide solution to calculate the total amount of F released. - ion;
[0086] S9: Take out the samples to be tested, and take out PEM-1-AST and PEM-2-AST respectively.
[0087] S10: The fuel cell engine is subjected to durability evaluation. After 1500 hours of actual testing, the membrane electrode is disassembled and PEM-1-Ageing and PEM-2-Ageing are taken out respectively.
[0088] S11: Perform surface density, thickness and air permeability tests on the initial samples PEM-1-Initial and PEM-2-Initial, the accelerated attenuation samples PEM-1-AST and PEM-2-AST, and the actual running attenuation samples PEM-1-Ageing and PEM-2-Ageing to observe the degree of sample attenuation caused by the ion (or solution).
[0089] like Figures 5 to 7As shown, two aging experiments were used, namely the accelerated aging attenuation method of this patent and the actual test attenuation. There were two test samples, PEM-1 and PEM-2. The test results were named as initial samples PEM-1-Initial and PEM-2-Initial, accelerated attenuation samples PEM-1-AST and PEM-2-AST, and actual running attenuation samples PEM-1-Ageing and PEM-2-Ageing. The measured surface density of PEM-1-AST was 1.84 mg / cm 2 The density of PEM-1-Ageing after actual aging is 1.82 mg / cm 2 The test results are similar; the measured surface density of PEM-2-AST is 2.45 mg / cm 2 The density of PEM-2-Ageing after actual aging is 2.46 mg / cm 2 , the test results are similar, that is, this test method can well simulate the actual attenuation situation. The test results of the same thickness and air permeability coefficient are similar. The test method provided by this patent well reflects the actual attenuation situation.
[0090] By collecting the condensate and analyzing the F - The ion concentration can be calculated to give F - The ion release amount was as follows: PEM-1 released 1.2075 mol; PEM-2 released 0.99216 mol. This shows that PEM-1 was severely attenuated, which was also verified in the offline characteristics.
[0091] After adopting the above scheme, the problem of metal ions and free radicals on proton exchange membrane and resin chemical aging test is solved. It can well simulate the actual attenuation situation. The test results of the same thickness and air permeability coefficient are similar, which well reflects the actual attenuation situation.
[0092] In the description of the present invention, it is necessary to understand that the terms "coaxial", "bottom", "one end", "top", "middle", "the other end", "upper", "one side", "top", "inside", "front", "center", "both ends" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0093] In the present invention, unless otherwise clearly stipulated and limited, the terms such as "installation", "setting", "connection", "fixation" and "screw-on" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. Unless otherwise clearly defined, ordinary technicians in this field can understand the specific meanings of the above terms in the present invention according to the specific circumstances.
[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device, characterized in that: have: Coordinated base and cover plates; The workpiece positioning area is arranged on the bottom plate and the cover plate, and the workpiece positioning area can position and encapsulate the sample to be tested.
2. The fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device according to claim 1, characterized in that: A frame is arranged on the outer periphery of the bottom plate, and the frame is sealed and connected to the cover plate.
3. The fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device as claimed in claim 2, characterized in that: The frame is provided with a series of positioning holes, and the frame is connected to the cover plate through the positioning holes and connecting bolts.
4. The test method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device according to claim 3, characterized in that: The steps include: 1) Prepare the solution to be tested; 2) After packaging the sample to be tested, place it in the fixture of the above-mentioned testing device; 3) preparing KOH solution; 4) Connect the entire device and perform leak detection; 5) Introduce gas to activate the sample to be tested; 6) Add the prepared test solution into the test device, replace the device for collecting the solution with KOH solution, and start the test; 7) Weigh the mass of the collected water and calculate the F ions; 8) Take out the sample to be tested and conduct further characterization and analysis on the sample.
5. The test method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device according to claim 4, characterized in that: In the above step 1), a solution of a specific concentration is prepared, and the solution is H2O2, Fenton solution, Al2(SO4)3, Fe2(SO4)3, CuSO4, Mg2SO4, Cr2(SO4)3 or NiSO4. If the metal element is to be investigated, its anion group is SO4. 2- .
6. The test method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device according to claim 5, characterized in that: In the above step 2), the fixture material does not contain metal element impurities, and the samples to be tested include PEM, CCM or GDE.
7. The test method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device according to claim 6, characterized in that: In the above step 4), first place pure water in the humidification and condensation devices, connect the entire device, and perform leak detection; set the temperature of the insulation belt to 110°C to ensure that the steam does not condense in the pipeline, and set a specific temperature of the solution to be tested.
8. The test method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device as claimed in claim 7, characterized in that: In the above step 5), the gas was introduced for 16 hours to activate the sample to be tested and to enable a test run; the gas flow rate is related to the area, and the gas flow rate is 0.01-0.5 slpm / cm 2 , the gas is an inactive gas.
9. The test method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging test device as claimed in claim 8, characterized in that: In the above step 6), after continuously passing the gas for 16 hours, the prepared solution to be tested is added to the test device, the device for collecting the solution is replaced with KOH solution, and a leak test is performed; the gas is passed for 10 to 500 hours; the gas flow rate is related to the area, and the gas flow rate is 0.01 to 0.5 slpm / cm 2 , the gas is inactive gas; and the test solution and KOH solution are replaced every 24 hours.
10. The testing method of the fuel cell catalyst layer and proton membrane chemical decay accelerated aging testing device according to claim 9, characterized in that: In the above step 7), the mass of the collected water is weighed, and the fluoride ion concentration in the retained potassium hydroxide solution is measured by ion chromatography to calculate the released F ions.